Microscopic Traffic Simulation using SUMO - Lopez, Pablo Alvarez; Wiessner, Evamarie; Behrisch, Michael; Bieker-Walz, Laura; Erdmann, Jakob; Flotterod, Yun-Pang; Hilbrich, Robert; Lucken, Leonhard; Rummel, Johannes; Wagner, Peter (Proceedings (IEEE Conference on Intelligent Transportation Systems), 2018)
Microscopic traffic simulation is an invaluable tool for traffic research. In recent years, both the scope of research and the capabilities of the tools have been extended considerably. This article presents the latest developments concerning intermodal traffic solutions, simulator coupling and model development and validation on the example of the open source traffic simulator SUMO.